Effects of romosozumab combined with routine therapy on pain relief, disease progression and adverse reactions in patients with postmenopausal osteoporosis: a systematic review and meta-analysis - Gao, Ge; Cui, Jian; Xie, Yuanyuan; Dong, Jing (Frontiers in Medicine, 2024)
Background: Postmenopausal osteoporosis (PMOP) increases fracture risk in women.Though traditional treatments are slow to act, combining romosozumab with conventional therapy shows promise. Despite its growing use, studies on effectiveness are limited. This study aims to systematically evaluate the combined therapy's impact on pain relief, disease progression, and adverse reactions in PMOP patients.Databases including PubMed, EMBASE, ScienceDirect, and the Cochrane Library were searched from their inception to September 2023 to identify randomized controlled trials (RCTs) evaluating the role of romosozumab in PMOP. Random or fixed effect models were employed for statistical analysis. Two reviewers independently assessed the quality of the included studies and extracted the data. The meta-analysis was conducted using RevMan 5.4 software.Results: Six RCTs with a total sample size of 17,985 cases were included. The incidence of vertebral fractures was compared and analyzed after 12 and 24 months of treatment. Romosozumab significantly reduced the incidence of vertebral fractures at 24 months (OR=0.36; 95% CI: 0.35-0.52) but not at 12 months (OR=0.39; 95% CI: 0.14-1.05).Romosozumab significantly decreased the incidence of vertebral fractures at 12 months (OR=0.39; 95% CI: 0.14-1.05) and 24 months (OR=0.36; 95% CI: 0.35-0.52). It was also associated with a decreased incidence of nonvertebral fractures (OR=0.79; 95% CI: 0.66-0.94) and clinical fractures at 24 months (OR=0.70; 95% CI: 0.59-0.82) compared to standard therapy. Romosozumab demonstrated a significant improvement in percentage change in bone mineral density (BMD) (mean difference (MD)=10.38; 95% CI: 4.62-16.14) and in hip joint BMD (MD=4.24; 95% CI: 2.92-5.56). There was no notable difference in adverse reactions compared to standard care (P>0.05). Funnel plots displayed a predominantly symmetrical pattern, suggesting no evidence of publication bias in the selected literature.Combining romosozumab with conventional therapy effectively treats PMOP, significantly reducing vertebral, non-vertebral, and clinical fractures while increasing BMD in the hip, femoral neck, and lumbar spine. However, further highquality studies are needed for validation.